Idea związku środkowoeuropejskiego w latach 30. XX wieku opartego na unii polsko-węgierskiej = The idea of central european alliance in the 30S of the 20th century on the foundation of Polish Hungarian union - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monthly newspaper 'Nasza Przyszlość', published since 1930 by Jan Bobrzyński, popularised the integration of the following countries: Bulgaria, Czechoslovakia, Estonia, Jugoslavia, Lithuania, Latvia and Romania, situated in the triangle of The Baltic Sea - The Black Sea - The Adriatic Sea under the direction of Poland, on the foundation of a union with Hungary. It excluded two countries: Austria and Greece.
Keywords: Europa Środkowo-Wschodnia; Nasza Przyszłość (czasopismo); 1918-1939